Quantitative and Qualitative Assessment of Adhesive Thrombo-Fibrotic Lead Encapsulations (TFLE) of Pacemaker and ICD Leads in Arrhythmia Patients—A Post Mortem Study - Keiler, Jonas; Schulze, Marko; Dreger, Ronja; Springer, Armin; Öner, Alper; Wree, Andreas (Frontiers in Cardiovascular Medicine, 2020)
The demand for cardiac implantable electronic devices for arrhythmia therapy is still unabated and rising. Despite onward optimizations, lead-related problems such as infections or fractures often necessitate lead extraction. Due to adhesive thrombo-fibrotic lead encapsulations (TFLE) transvenous lead extraction is challenging and risky. However, knowledge on TFLEs and possible correlations with technical lead parameters and dwelling time (DT) were hitherto insufficiently studied. Therefore, we analyzed TFLEs of 62 lead from 35 body donor corpses to gain information for a potential lead design optimization. We examined both TFLE topography on the basis on anatomical landmarks and histo-morphological TFLE characteristics by means of histological paraffin sections and scanning electron microscopy of decellularized samples. The macroscopic analysis revealed that all leads were affected by TFLEs, mainly in the lead bearing veins. Half (47.2%) of the right-ventricular leads possessed adhesions to the tricuspid valve. On average, 49.9 ± 21.8% of the intravascular lead length was covered by TFLE of which 82.8 ± 16.2% were adhesive wall bindings (WB). The discrete TFLEs with at least one WB portion had a mean length of 95.0 ± 64.3 mm and a maximum of 200 mm. Neither sex, DT nor certain technical lead parameters showed distinct tendencies to promote or prevent TFLE. TFLE formation seems to start early in the first 1–2 weeks after implantation. The degree of fibrotization of the TFLE, starting with a thrombus, was reflected by the amount of compacted collagenous fibers and likewise largely independent from DT. TFLE thickness often reached several hundred micrometers. Calcifications were occasionally seen and appeared irregularly along the TFLE sheath. Leadless pacemaker systems have the advantage to overcome the problem with TFLEs but hold their own specific risks and limitations which are not fully known yet.